Why and how to engage students in the learning process; SEFI 2015 : proceedings of the 43rd SEFI Annual Conference 2015, 29 June-2 July 2015, Orlean - Pokholkov Y. P. Yuri Petrovich (Diversity in Engineering Education, 2015)
Title screen